Perceived motivational climate and self-determined motivation in male and female high school athletes - Amorose, A. J. (Research Quarterly for Exercise and Sport, 2005)
Das Ziel der Studie war die Bestimmung des Zusammenhangs zwischen den Ausmaßen des empfundenen Motivationsklimas und der vom Athleten selbst bestimmten Motivation.